Collaborative Governance Dalam Pelayanan Publik : Studi Gerbang Penyandang Disabilitas Sukses di Kabupaten Banyumas - Titin Lestari Lestari; Slamet Rosyadi; Tobirin Tobirin (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
The research was motivated because there are social problems in the form of access to employment opportunities for people with productive age disabilities in Banyumas Regency that cannot be resolved alone by local government, so collaborative governance efforts are needed together with non-government through Program Gerbang Penyandang Disabilitas Sukses (Gendis). This research to describe collaborative in the Program Gendis based on the collaborative governance theory of Rusell M.Linden through five stages: 1) Basic collaboration, 2)Relationship, 3) High stakes, 4) Consistuency for collaboration, 5) Collaborative leadership. The methods used in this study are descriptive with a qualitative approach. The research findings that Program Gendis has not been optimal because coordination and communication that can be the main key to forming collaboration and building trust do not have a clear direction resulting in synergy from stakeholders who have not formed bond with each other.